El emprendimiento factor determinante en la competitividad y la perdurabilidad de las empresas (2014)
This paper presents a vision that integrates entrepreneurship as a basis for creating sustainable and lasting enterprises, interest motivates us to bring the idea in the sense of the need to ensure better people for a greater number of new firms, only if achieves better people grounded in personal enterprise; If this view is welcomed surely find echoes in reducing the mortality of companies to the first, second or even third year of implementation.